Effect of Beet Powder (Beta Vulgaris L) with Fe Supplementation on Increasing Hemoglobin, Hematocrit, and Erythrocyte Levels in Pregnant Women with Anemia - Hilma Triana; Suharyo Hadisaputro; Masrifan Djamil (STRADA : Jurnal Ilmiah Kesehatan, 2020)
This research was Quasy Experiment with a pre-test-post-test with control group design. Sample this research was 30 pregnant women, that were divided into 2 groups : the intervention group who were given beet with Fe supplementation (n = 15) and the control group was given Fe tablets (n = 15). Supplementation of beetroot to a pregnant women with anemia who were recieived Fe supplementation could increase hemoglobin levels (p = 0,000), hematocrit levels (p = 0,000), number of erythrocytes (p = 0.001), so there were significant differences in mean delta hemoglobin levels, hematocrit, and erythrocyte counts. There were differences in hemoglobin and erythrocyte levels in the intervention and control groups before and after treatment. Supplementation of 8 gram beetroot powder for 14 days to pregnant mother with anemia who were receive Fe tablets could increase hemoglobin and hematocrit levels, and number of erythrocytes